2010
DOI: 10.1002/lapl.200910122
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the flow of light with silicon nanostructures

Abstract: Silicon is an important material for integrated photonics applications. High refractive index and transparency in the infrared region makes it an ideal platform to implement nanostructures for novel optical devices. We fabricated silicon photonic crystals and experimentally demonstrated negative refraction and self-collimation. We also used heterodyne near-field scanning optical microscope to directly visualize the anomalous wavefronts. When the periodicity is much smaller than wavelength, silicon photonic cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These artificially created crystals demonstrated many unique phenomena which cannot be observed in natural world. Some of the unique phenomena include negative refraction 4-7 , self-collimation [8][9][10] , super-prism 11,12 , strong light confinement 13,14 and slow light 15 , etc. These unique features possess high potential to contribute to the future development of photonics technology.…”
Section: Introductionmentioning
confidence: 99%
“…These artificially created crystals demonstrated many unique phenomena which cannot be observed in natural world. Some of the unique phenomena include negative refraction 4-7 , self-collimation [8][9][10] , super-prism 11,12 , strong light confinement 13,14 and slow light 15 , etc. These unique features possess high potential to contribute to the future development of photonics technology.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the phenomena of transmission enhancement have been observed when light passes through periodic or aperiodic arrays, sub-wavelength apertures, split rings, self-assembled nanoparticle clusters and coupled nanoholes [13][14][15][16]. Among various geometric shapes, the metal grating has been considered as one of the simplest metal-dielectric structures, which has been studied extensively for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Although many efforts have been made in theoretical and experimental investigations, the physical mechanism for the enhanced optical transmission is still controversial due to their complexity and sensitivity to the shapes, polarization of terahertz (THz) radiation and interpretation methods [17]. Some researchers suggested that the anomalous transmission of gratings arises from the excitation of surface plasmon polaritons (SPPs) [2,4,6,13,16]. Others attributed the extraordinary transmission to the excitation of waveguide mode resonance and considered that the SPPs play a negative role in the transmission of metallic gratings [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These microstructures can change the properties of silicon material dramatically. 1,2) Particularly, the light absorption property in the infrared range (>0:8 m) can be remarkably enhanced to more than 90%, 3,4) which can be widely utilized in various applications, such as solar cells, 5) terahertz emission, 6) negative refraction of light, 7) and optoelectronic detectors. [8][9][10][11] Therefore, many efforts have been devoted to the fabrication of microstructured silicon with different surface morphologies for the larger photoelectric absorption coefficient, including the laser fluence, 12) pulse width, 13,14) polarization, 15) pulse number, 16) wavelength, 17) ambient gas, 18) and gas pressure.…”
mentioning
confidence: 99%